2021
DOI: 10.1101/2021.07.30.454432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular dissection of carbapenem-resistant Acinetobacter baumannii circulating in Indian hospitals using Whole Genome Sequencing

Abstract: Objectives: Carbapenem-resistant Acinetobacter baumannii (CRAB) has acquired worldwide recognition as a serious nosocomial infection. It poses a concern to hospitalized patients because of the limited therapeutic options available. Thus, we investigated the molecular epidemiology and antibiotic resistance profiles of A. baumannii isolates in India. Materials and Methods: We characterized 306 retrospective A. baumannii clinical isolates collected from 18 centers across 10 states and 1 Union Territory of India b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…The major genetic determinant of carbapenem resistance among our isolates was the bla OXA-23-like gene followed by bla NDM-1 . A similar trend has been reported among CRAB isolates in many previous studies from India [9–11, 31–33]. OXA-23 group was the first group of carbapenem-hydrolysing oxacillinases to be identified in A.…”
Section: Discussionsupporting
confidence: 85%
“…The major genetic determinant of carbapenem resistance among our isolates was the bla OXA-23-like gene followed by bla NDM-1 . A similar trend has been reported among CRAB isolates in many previous studies from India [9–11, 31–33]. OXA-23 group was the first group of carbapenem-hydrolysing oxacillinases to be identified in A.…”
Section: Discussionsupporting
confidence: 85%
“…Among Acinetobacter spp., the presence of the bla GES–11 (ESBL-genotype and weak carbapenemase) and the OXA-51-like ( bla OXA–66 and bla OXA–69 ) carbapenemases encoding genes is a serious threat. The OXA-51-like intrinsic carbapenemase encoding ST1 A. baumannii Isolates were reported from India ( Rose et al, 2021 ), but isolates from the present study encoded additionally the weakly carbapenem hydrolyzing bla GES–11 gene. The bla GES–11 ESBL-genotypes, and the bla OXA–51 -like carbapenemases have not been previously reported from Ethiopia, and the present study is to our knowledge the first report of bla OXA–51 like and bla GES–11 from Ethiopia.…”
Section: Discussionmentioning
confidence: 55%
“…The ST1089 (IC9) strains were the second most common lineage in this study. These strains have been isolated from clinical samples and hospital environments, particularly from studies in Northern Africa and in the Middle East, and are frequently reported to carry blaNDM-1 and blaOXA-94 carbapenem resistance genes (32,(33)(34)(35)(36)(37)(38)(39). An ST1089 strain carrying blaNDM-1 was also isolated from raw milk in a dairy farm in Algeria (40).…”
Section: Discussionmentioning
confidence: 99%